An investigation of the efficacy of a polyvalent mastitis vaccine using different vaccination regimens under field conditions in the United Kingdom - Bradley, Andrew J.; Breen, J.E.; Payne, B.; White, V.; Green, Martin J. (American Dairy Science Association, 2015)
Vaccination can play a useful role in mastitis control programs, although there is a relative dearth of large, well-controlled field efficacy studies. This paper presents the findings on the use of a commercially available vaccine (Startvac, Hipra UK Ltd., Nottingham, UK) on commercial units under UK field conditions. In total, 3,130 cows were recruited from 7 farms and were randomly allocated, within farm, to 1 of 3 groups. The first group received the vaccine following the label regimen, the second group was vaccinated every 90 d following an initial vaccination course, and the third group was left unvaccinated to act as controls. Vaccine efficacy was assessed in the first 120 d of lactation. Data were available for analysis from 1,696 lactations in 1,549 cows. In total, 779 cases of clinical mastitis occurred in the 3 study groups, and we detected no significant difference in the incidence or prevalence of clinical or subclinical mastitis between any of the 3 groups. Mastitis vaccination following the label regimen was associated with a significant reduction in the severity of clinical cases. Cows in this group were at significantly decreased odds of developing clinical mastitis presenting with more than just milk changes [odds ratio: 0.58; 95% confidence interval (CI): 0.35–0.98]. Similarly, each additional vaccination resulted in a cow being at decreased odds of developing clinical mastitis presenting with more than just milk changes (odds ratio: 0.87; 95% CI: 0.77–0.98). Although no cows were culled because of severe mastitis in either of the vaccinated groups, we detected no significant difference in the mastitis-related culling rate between groups. Analysis of milk production data demonstrated that, on average, cows on the label regimen produced a higher volume of milk (231 L; 95% CI: 104.1–357.4) and more milk solids (12.36 kg; 95% CI: 3.12–21.60) than unvaccinated cows in the first 120 d of lactation. Conservative analysis suggested that a return on investment of 2.57:1 could be expected under UK conditions based on increased milk yield alone.